دراسة توزع الدفع الجانبي للتربة على الجدران الاستنادية من أجل ردم خلفي محدود العرض - منذر عمران الزاوي (Tishreen University, 2019)
يهتم هذا البحث بدراسة شكل توزع دفع التربة المفككة ذات العرض المحدود على الحواجز والجدران الاستنادية نظراً إلى أن نظرية كولومب أو رانكين لاتصلحان لمثل هذه الحالات وتعطيان قيماً أكبر من الحقيقة، ومن أجل ذلك تم بناء صندوق اختبار خاص (موديل تجريبي) من أجل قياس دفع التربة على الحواجز، جربت فيه عدة أنواع من الترب المفككة الخشنة المأخوذة من مناطق مختلفة , وبينت نتائج الاختبارات أن نوع التربة المفككة لايؤثر كثيراً على شكل مخطط الضغط، بينما يلعب عرض المجال المحصور دوراً كبيراً في تحديد شكل وقيمة مخطط توزع الضغط, وأمكن عن طريق رصد سطوح الانزلاق المتشكلة في أثناء التجربة وشكل المنحني الحقيقي للتجربة اقتراح طريقة تقريبية لحساب ورسم مخطط توزع ضغط التربة المحصورة على الحواجز بدلالة عرض المجال المحصور. This research includes the study of the distribution form of the earth pressure with limited width backfill hinter retaining walls, whereas both Coloumb's and Rankin's theory is useless for such cases, and they give greater values than reality, so a special experimental box (an experimental model) was built in which various types of rough loose soil from different regions was experimented to measure the earth pressure on walls. The test results showed that the type of the loose soil doesn't affect the shape of the pressure diagram. However, the width of the limited range of backfill has a great role to define the value and shape of the real earth pressure distribution diagram and it was possible to propose an simplified method to calculate and draw a diagram of the limited earth pressure distribution on retaining walls by using the width of the limited range.